Sistem Penyiraman Tanaman Otomatis Menggunakan Sensor Kelembaban Tanah Pada Arduino Dengan Menerapkan Metode Prototyping - Sadam; Muhammad Cordiaz (CV. Multi Kreasi Media, 2024)
The development of technology and the application of sophisticated systems is growing very rapidly. Many people need one type of tool that is used for watering plants to measure soil moisture using Arduino on plants. In this study, the author will design an automatic plant watering system using Arduino and a moisture sensor as a measure of soil moisture in plants. In this study, a soil moisture sensor is used which functions to identify the water content in the soil and an Arduino Uno as a microcontroller in this design. Based on the results of the tests carried out, the watering carried out by this design has the advantage that it can water plants automatically.